Calmodulinopathy: A Novel, Life-Threatening Clinical Entity Affecting the Young - Kotta, Maria-Christina; Sala, Luca; Ghidoni, Alice; Badone, Beatrice; Ronchi, Carlotta; Parati, Gianfranco; Zaza, Antonio; Crotti, Lia (Frontiers in Cardiovascular Medicine, 2018)
Sudden cardiac death (SCD) in the young may often be the first manifestation of a genetic arrythmogenic disease that had remained undiagnosed. Despite the significant discoveries of the genetic bases of inherited arrhythmia syndromes, there remains a measurable fraction of cases where in-depth clinical and genetic investigations fail to identify the underlying SCD etiology. A few years ago, 2 cases of infants with recurrent cardiac arrest episodes, due to what appeared to be as a severe form of long QT syndrome (LQTS), came to our attention. These prompted a number of clinical and genetic research investigations that allowed us to identify a novel, closely associated to LQTS but nevertheless distinct, clinical entity that is now known as calmodulinopathy. Calmodulinopathy is a life-threatening arrhythmia syndrome, affecting mostly young individuals, caused by mutations in any of the 3 genes encoding calmodulin (CaM). Calmodulin is a ubiquitously expressed Ca2+ signaling protein that, in the heart, modulates several ion channels and participates in a plethora of cellular processes. We will hereby provide an overview of CaM’s structure and function under normal and disease states, highlighting the genetic etiology of calmodulinopathy and the related disease mechanisms. We will also discuss the phenotypic spectrum of patients with calmodulinopathy and present state-of-the art approaches with patient-derived induced pluripotent stem cells that have been thus far adopted in order to accurately model calmodulinopathy in vitro, decipher disease mechanisms and identify novel therapies.